Does adding water to a dry starter diet improve calf performance during winter?. (10th October 2018) - Beiranvand, H.; Khani, M.; Ahmadi, F.; Omidi-Mirzaei, H.; Ariana, M.; Bayat, A. R.
Abstract : Very recently, we added water to a dry texturized starter diet and found substantial improvements in calf performance during summer, leading to the hypothesis that the wet starter diet would also benefit calf performance during winter. Forty-five 3-day-old male Holstein calves (BW 43.4±3.4 kg) were blocked by initial BW and distributed randomly to one of three starter diets (1 calf per pen; 15 pens per treatment) that differed only in moisture content as 90%, 75% and 50% dry matter (DM; DM90, DM75 and DM50, respectively). The starter diet comprised 55.1% ground ingredients (soybean meal, barley and corn gluten meal), 21.9% whole corn, 10% rolled barley and 10% chopped alfalfa hay. The mean ambient temperature averaged 2.1±0.9°C during the 70-day experiment. Calves were weaned at day 50 of the study. Although starter feed intake remained unaffected by treatment, the calves receiving DM75 and DM50 consumed more starter feed (DM basis) than those receiving DM90 diet during the first 20 days of the experiment. Body weight at weaning exhibited a quadratic response with the heaviest weaning weight (76.8 kg) occurring when calves consumed DM75 diet. Adding water to the dry starter diet tended to linearly increase final BW. Average daily gain during the pre- (0.67 kg/day) and post-weaning (1.22 kg/day) periods was the greatest for calves receiving DM75 and DM50, respectively. Although feed efficiency during the pre-weaning and overall periods did not differ across the treatments, a quadratic effect was detected in the post-weaning feed efficiency, with the lowest value being observed with DM75 diet. No difference was noted on skeletal growth parameters measured on days 50 and 70. Adding water to the dry starter diet linearly increased total volatile fatty acids concentration in the rumen. No difference among treatments existed in calf behavior recorded on days 35 and 70. As moisture content of the starter diet increased, the extent of sorting for long particles (>2 mm) and against fine particles (<0.125 mm) decreased. During the 70-day winter trial, adding water to the dry texturized starter diet with 10% chopped alfalfa hay resulted in a higher feed intake during the first weeks of life, a quadratic tendency toward improved growth rate during the pre-weaning period, and possibly a more functional rumen fermentation. A wet starter diet with 75% DM in the physical form offered in this study can be recommended to improve calf performance during winter.